Kirk Wong's Hong Kong Crimes - Stokes, Lisa Odham and Hoover, Michael (Asian Cinema, 2002)
While John Woo, Ringo Lam, and Tsui Hark have become well known names in the West, Hong Kong director Kirk Wong has yet to break into the mainstream. His 1998 black comedy The Big Hit didn't score big enough with Western audiences although it did a respectable business, budgeted at $13 million and grossing $27 million in the US that year (double its production cost). But a look at Wong's dark vision in earlier Hong Kong films provides a partial explanation for his dark horse status. In Wong films, action emerges from characters' emotional conflicts, carrying them forward towards narrative resolution.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9hYy4xMy4yLjc2XzE